Psychotherapy of Anxiety: Value Oriented Approach - Ilya V Zakharov (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2017)
The article outlines the principal theses of the concept of psychotherapy of anxiety disorders, based on changing the client's perception on his problem and revising the system of values. Model of "anxiety-centered" behavior is reviewed and ways of transformation of client's self-evaluation and lifestyle that are to manage the anxiety are described. Changing the "reference system" as core element of recovery is reviewed. Material is illustrated with case studies and excerpts from therapeutic sessions.